Where the truth lies - Warman, Jessica (New York : Walker Books for Young Readers : Distributed to the trade by Macmillan, 2010)
Emily, whose father is headmaster of a Connecticut boarding school, suffers from nightmares, and when she meets and falls in love with the handsome Del Sugar, pieces of her traumatic past start falling into place.
Keywords: Nightmares -- Fiction; Memory -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Dating (Social customs) -- Fiction; Family life -- Connecticut -- Fiction; Connecticut -- Fiction